Preparation method of super-hydrophobic attapulgite-based slow-release urea
Superhydrophobic concave and concave rock powder was prepared by silane coupling agent treatment and ethanol solution treatment, combined with lard coating and polyether polyol binder, and the existing slow release urea was solved. The complex and costly preparation of release fertilizers has achieved efficient urea sustained release and cost reduction.
Patent Information
- Application Number
- CN202411697994.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The preparation process of existing sustained-release fertilizers is complex and costly, and the organic polymer coating is difficult to recover and degrade, affecting the soil ecosystem.
After the surface modification of the concave and concave and concave powder is modified with silane coupling agent, it is treated with ethanol, ammonia and octyltrimethylsilane solution to form a superhydrophobic concave and concave and concave powder. The urea granules were then coated with lard and a mixture of polyether polyol and polymethylene polyphenylene isocyanate was used as the binder to form a superhydrophobic concave-concave-rodite-based sustained-release urea.
Through the synergistic effect of the hydrophobic properties of superhydrophobic concave and convex rock stones and the multi-layer membrane structure, the release of nitrogen elements in urea is delayed, and the sustained release effect is achieved, while reducing the preparation cost and simplifying the process flow.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of slow-release fertilizers, and in particular relates to a method for preparing super-hydrophobic attapulgite-based slow-release urea. Background Art
[0002] Slow-release fertilizers refer to fertilizers that prolong the release time of effective nutrients through chemical compounding or physical action on the nutrients contained in the fertilizer. Slow-release fertilizers are mainly divided into slightly soluble organic compound fertilizers, slightly soluble inorganic fertilizers and physical barrier controlled release fertilizers according to their nutrient control release mode, coating material type, preparation principle and process.
[0003] The use of organic polymer coating to prepare slow-release fertilizers is costly, and the polymers are difficult to recycle and degrade, which can easily damage the soil ecosystem and cause secondary pollution. In recent years, the research on super-hydrophobic materials with special wettability has provided new ideas for the preparation of slow-release fertilizers. However, the preparation process of existing super-hydrophobic slow-release fertilizers is often complicated and costly, which limits their promotion and application in agricultural production.
[0004] Attapulgite is a hydrous magnesium-rich aluminum silicate mineral with a layered chain structure. Due to its special crystal structure and unusual colloidal properties, adsorption properties, and carrier properties, it can be processed into a soil conditioner, used as an improver, adhesive, and suspending agent, which can enhance the soil's ability to retain water and fertilizer. In addition to its main components of Si, Al, Mg and other elements, attapulgite also contains essential nutrients for organisms such as Na, K, Fe, etc. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing super-hydrophobic attapulgite-based slow-release urea, so as to solve the problems that the cost of preparing slow-release fertilizers by organic polymer coating is relatively high, and the polymer is difficult to recycle and degrade.
[0006] The technical solution of the present invention is: a method for preparing super-hydrophobic attapulgite-based sustained-release urea, comprising the following steps: A. Grinding and sieving attapulgite to obtain attapulgite powder; B. Using ethanol as solvent, adding ammonia water and octyltrimethylsilane to mix evenly, then immersing the attapulgite powder in the mixed solution, discarding the upper layer of liquid after standing, drying, grinding, and sieving to obtain super-hydrophobic attapulgite powder; C. Put urea in a coating machine, heat and melt lard and mix it with urea, and form an inner lard film on the surface of urea particles after coating to obtain primary coated urea particles; D. mixing polyether polyol and polymethylene polyphenyl isocyanate, heating them, and mixing them well to obtain an adhesive; E. Spray the binder onto the surface of the primary coated urea particles with a spray gun, then add the super-hydrophobic attapulgite powder, and obtain the super-hydrophobic attapulgite-based sustained-release urea after coating.
[0007] As a further improvement of the present invention, in step B, ethanol is used with a volume fraction of 95%, and the volume ratio of ethanol, ammonia water and octyltrimethylsilane is 100:1-5:5-10.
[0008] As a further improvement of the present invention, in step B, the volume mass ratio of ethanol to attapulgite powder is 1000 mL:300-500 g.
[0009] As a further improvement of the present invention, in step A, the product is sieved through a 200-mesh sieve.
[0010] As a further improvement of the present invention, in step B, the standing time is 24-36 hours.
[0011] As a further improvement of the present invention, in step C, the mass ratio of urea to lard is 18-20:1.
[0012] As a further improvement of the present invention, in step D, the volume ratio of the polyether polyol to the polymethylene polyphenyl isocyanate is 2-3:1.
[0013] As a further improvement of the present invention, in step D, the heating temperature is 80-85°C.
[0014] The beneficial effects of the present invention are: 1. The present invention uses attapulgite as a raw material, utilizes the natural micro-nano composite hierarchical structure on its surface, and obtains super-hydrophobic attapulgite powder after surface modification with a silane coupling agent; uses a mixture of polyether polyol and polymethylene polyphenyl isocyanate as an adhesive, sprays urea particles treated with lard, adds super-hydrophobic attapulgite powder, and makes super-hydrophobic attapulgite-based slow-release urea after coating treatment. The hydrophobic property of the super-hydrophobic attapulgite surface blocks the penetration of soil pore water, thereby delaying the release of nitrogen in urea, and playing a slow-release effect.
[0015] 2. The present invention uses attapulgite powder as raw material, and obtains super-hydrophobic attapulgite powder after being treated with a silane coupling agent. The good adsorption and super-hydrophobicity of attapulgite powder are utilized to improve the density, uniformity and sustained-release properties of the film product, thereby obtaining an excellent sustained-release effect.
[0016] 3. The present invention coats urea particles with melted lard to form an inner membrane; uses a mixture of polyether polyol and polymethylene polyphenyl isocyanate as an adhesive and coats super-hydrophobic attapulgite powder to form an outer membrane. The lard of the inner membrane is a low surface energy material that can effectively prevent water from entering; the hydrophobicity of the super-hydrophobic attapulgite of the outer membrane can also effectively prevent water from entering; the synergistic effect of the inner membrane and the outer membrane can effectively improve the sustained release of the obtained product.
[0017] 4. The present invention has the advantages of easy availability of raw materials, simple preparation process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a scanning electron microscope image of the super-hydrophobic attapulgite-based sustained-release urea prepared in Example 1 of the present invention; Figure 2 This is the urea content release diagram of common agricultural urea in water; Figure 3 This is a graph showing the urea content release of the super-hydrophobic attapulgite-based sustained-release urea prepared in Example 1 of the present invention in water; Figure 4 is a scanning electron microscope image of the super-hydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention after being immersed in water; Figure 5 This is a comparison chart of plant height data measured at different times after the superhydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and common agricultural urea were applied to wheat; Figure 6 This is a comparison diagram of the growth morphology of the super-hydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and common agricultural urea after being applied to wheat at different times; Figure 7 This is a comparison chart of the ear emergence rate of wheat after the super-hydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and the common agricultural urea were applied to the wheat; Figure 8 This is a comparison chart of the quality of wheat grains harvested after the superhydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and common agricultural urea were applied to wheat. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with specific implementation modes.
[0020] Embodiment 1, A method for preparing super-hydrophobic attapulgite-based slow-release urea comprises the following steps: A. Grinding attapulgite and passing it through a 200-mesh sieve to obtain attapulgite powder; B. Use 1000 mL of 95% ethanol by volume as solvent, add 10.00 mL of ammonia water and 50.00 mL of octyltrimethylsilane and mix well, then immerse 300 g of attapulgite powder in the mixed solution, stir for 20-30 h, let stand for 24 hours, discard the upper layer liquid, dry at 85 ° C, grind and sieve to obtain superhydrophobic attapulgite powder; C. Put urea in a coating machine, heat lard at 45°C to melt and mix with urea, the mass ratio of urea to lard is 18:1, and after rotating at 40-60 rpm for coating treatment, an inner lard film is formed on the surface of urea particles to obtain primary coated urea particles; D. Mixing polyether polyol and polymethylene polyphenyl isocyanate in a volume ratio of 2:1, heating at 80° C. for 10 minutes, and mixing well to obtain an adhesive; E. Spray the binder onto the surface of the primary coated urea particles with a spray gun, then add the super-hydrophobic attapulgite powder, and rotate the coating machine at 65° C. and 40-60 rpm to obtain super-hydrophobic attapulgite-based sustained-release urea.
[0021] The super-hydrophobic attapulgite-based sustained-release urea prepared in this embodiment has a contact angle of water droplets on its surface exceeding 150°, showing excellent super-hydrophobicity.
[0022] The scanning electron microscope image of the super hydrophobic attapulgite-based slow-release urea prepared in this embodiment is as follows: Figure 1 shown.
[0023] (I) Test of sustained release of super-hydrophobic attapulgite-based urea: 10.00 g of original common agricultural urea granules and 10.00 g of super-hydrophobic mixed-dimensional attapulgite-based urea granules prepared in this example were placed in 100-mesh stainless steel mesh bags and immersed in 200.00 mL of distilled water. The quality of urea in water was tested by spectrophotometry. The results showed that the absorbance of common agricultural urea was tested every 10 s. After 50 s, the quality of urea no longer changed. Figure 2 As shown; the absorbance of the super-hydrophobic attapulgite-based slow-release urea in this embodiment was tested every 8 h. After 108 h, the quality of urea no longer changed, as shown in FIG. Figure 3 Compared with ordinary agricultural urea granules, the release time of superhydrophobic attapulgite-based slow-release urea granules is 7776 times that of ordinary agricultural urea granules.
[0024] After the superhydrophobic attapulgite-based slow-release urea is soaked in water, the urea in the core dissolves and pores are formed on the surface of the superhydrophobic attapulgite, such as Figure 4 shown.
[0025] (II) Potted plant experiment: After wheat was sown, the wheat that was treated with common agricultural urea grew out of the soil surface after 4 days, and the wheat that was treated with superhydrophobic attapulgite-based slow-release urea grew out of the soil surface after 3 days. The height of the wheat seedlings was measured after they grew out of the soil surface. The heights measured at different times are shown in Figure 2. Figure 5 As shown in the figure, the height of the wheat seedlings applied with superhydrophobic attapulgite slow-release urea is higher than that of ordinary agricultural slow-release urea.
[0026] Figure 6 FIG. 1 is a comparison of the growth morphology of the superhydrophobic attapulgite-based slow-release urea prepared in this embodiment and the common agricultural urea after being applied to wheat at different times. The growth morphology of wheat on the 3rd, 20th, 50th and 70th days after planting is as follows: Figure 6 As shown. The test shows that in the growth stage after wheat germination, the wheat seedlings applied with superhydrophobic attapulgite-based slow-release urea grew rapidly, and the plant height was higher than that of wheat applied with ordinary agricultural urea. After 20 days, the growth rate of wheat applied with original urea was slow, and the growth of wheat applied with superhydrophobic attapulgite-based slow-release urea was relatively fast. The growth state of wheat seedlings applied with superhydrophobic attapulgite-based slow-release urea was better than that of wheat seedlings applied with ordinary agricultural urea.
[0027] Figure 7 : is a comparison chart of the ear emergence rate of wheat after the super-hydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and the common agricultural urea were applied to the wheat, as shown in FIG. Figure 7 As shown, the heading rate of wheat seedlings treated with superhydrophobic attapulgite-based slow-release urea is higher than that of wheat seedlings treated with ordinary agricultural urea.
[0028] Figure 8 : is a comparison chart of the quality of wheat grains harvested after the super-hydrophobic attapulgite-based slow-release urea prepared in Example 1 of the present invention and the common agricultural urea were applied to wheat, as shown in FIG. Figure 8 As shown, the seed mass of wheat harvested after application of superhydrophobic attapulgite-based slow-release urea is higher than that of wheat harvested after application of ordinary agricultural urea.
[0029] Embodiment 2, A method for preparing super-hydrophobic attapulgite-based slow-release urea comprises the following steps: A. Grinding attapulgite and passing it through a 200-mesh sieve to obtain attapulgite powder; B. Use 1000 mL of 95% ethanol by volume as solvent, add 20.00 mL of ammonia water and 80.00 mL of octyltrimethylsilane and mix well, then immerse 500 g of attapulgite powder in the mixed solution, stir for 20-30 h, let stand for 36 hours, discard the upper layer liquid, dry at 85 ° C, grind and sieve to obtain superhydrophobic attapulgite powder; C. Put urea in a coating machine, heat lard at 45°C to melt and mix with urea, the mass ratio of urea to lard is 19:1, and after rotating at 40-60 rpm for coating treatment, an inner lard film is formed on the surface of urea particles to obtain primary coated urea particles; D. Mixing polyether polyol and polymethylene polyphenyl isocyanate in a volume ratio of 3:1, heating at 85° C. for 10 minutes, and mixing well to obtain an adhesive; E. Spray the binder onto the surface of the primary coated urea particles with a spray gun, then add the super-hydrophobic attapulgite powder, and rotate the coating machine at 65° C. and 40-60 rpm to obtain super-hydrophobic attapulgite-based sustained-release urea.
[0030] Embodiment 3, A method for preparing super-hydrophobic attapulgite-based slow-release urea comprises the following steps: A. Grinding attapulgite and passing it through a 200-mesh sieve to obtain attapulgite powder; B. Use 1000 mL of 95% ethanol by volume as solvent, add 50.00 mL of ammonia water and 100.00 mL of octyltrimethylsilane and mix well, then immerse 400 g of attapulgite powder in the mixed solution, stir for 20-30 h, let stand for 28 hours, discard the upper layer liquid, dry at 85 ° C, grind and sieve to obtain superhydrophobic attapulgite powder; C. Put urea in a coating machine, heat lard at 45°C to melt and mix with urea, the mass ratio of urea to lard is 20:1, and after rotating at 40-60 rpm for coating treatment, an inner lard film is formed on the surface of urea particles to obtain primary coated urea particles; D. Mixing polyether polyol and polymethylene polyphenyl isocyanate in a volume ratio of 2.5:1, heating at 82° C. for 10 minutes, and mixing well to obtain an adhesive; E. Spray the binder onto the surface of the primary coated urea particles with a spray gun, then add the super-hydrophobic attapulgite powder, and rotate the coating machine at 65° C. and 40-60 rpm to obtain super-hydrophobic attapulgite-based sustained-release urea.
Claims
1. A method for preparing superhydrophobic attapulgite-based slow-release urea, characterized in that The following steps are involved: A. Grinding and sieving attapulgite to obtain attapulgite powder; B. Using ethanol as solvent, adding ammonia water and octyltrimethylsilane to mix evenly, then immersing the attapulgite powder in the mixed solution, discarding the upper layer of liquid after standing, drying, grinding, and sieving to obtain super-hydrophobic attapulgite powder; C. Put urea in a coating machine, heat and melt lard and mix it with urea, and form an inner lard film on the surface of urea particles after coating to obtain primary coated urea particles; D. mixing polyether polyol and polymethylene polyphenyl isocyanate, heating them, and mixing them well to obtain an adhesive; E. Spray the binder onto the surface of the primary coated urea particles with a spray gun, then add the super-hydrophobic attapulgite powder, and obtain the super-hydrophobic attapulgite-based sustained-release urea after coating.
2. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step B, ethanol is used with a volume fraction of 95%, and the volume ratio of ethanol, ammonia water and octyltrimethylsilane is 100:1-5:5-10.
3. A method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 2, characterized in that: In step B, the volume mass ratio of ethanol to attapulgite powder is 1000 mL:300-500 g.
4. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step A, pass through a 200 mesh screen.
5. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step B, the standing time is 24-36 hours.
6. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step C, the mass ratio of urea to lard is 18-20:
1.
7. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step D, the volume ratio of the polyether polyol to the polymethylene polyphenyl isocyanate is 2-3:
1.
8. The method for preparing a super-hydrophobic attapulgite-based slow-release urea according to claim 1, characterized in that: In step D, the heating temperature is 80-85°C.